Failure mechanism and dynamic process of landslide triggered debris flows—an example from Chongqing, China - Wang, Fen; Dai, Zhenwei; Zhang, Anle; Cheng, Shi; Xiong, Qihui (Frontiers in Earth Science, 2024)
Shallow landslides and debris flows triggered by heavy rainfall are widespread catastrophic geological disasters in mountainous areas. Landslides with complex terrain are often the material source of debris flows as a disaster chain. However, the failure mechanism and dynamic process of landslide triggered debris flow are still not clear. In July 2023, an obvious rockslide occurred during heavy rainfall in Changtan Town, Chongqing City, Southwest China, resulting in one death and seven houses collapsed. In this paper, back analysis in the dynamic process of the Yanghuachi (YHC) landslide triggered debris flow is carried out by the coupled particle flow model and elastic viscoplastic model. The reults indicate that the sliding body moves downward along the sliding surface, pushing the loose deposits at the lower part of the landslide to slip and then extending along the gully to the right bank of the Modao River. The overall movement duration of the landslide in the study area is approximately 180 s, with a maximum sliding velocity of about 22.08 m/s and a final deposition thickness of approximately 10.91 m. This study provides a methodology for analyzing the dynamic process of landslide triggered debris flows.